114 A CASE OF AUTOSOMAL RECESSIVE INFANTILE OSTEOPETROSIS DUE TO MUTATION IN TCIRG1 PRESENTING WITH MULTIPLE CONGENITAL ANOMALIES. (1st January 2006) - Conway, R.; Lachman, R.; Hurvitz, C.; Falk, R.
Abstract : Autosomal recessive infantile osteopetrosis (ARIO) is a rare and potentially fatal disorder of bone metabolism caused by a defect in osteoclast function. The pathologic features are secondary to insufficient bone resorption and usually present in the infancy. Symptoms include sclerotic bones leading to bone marrow compromise with resultant pancytopenia, cranial nerve impingement, hydrocephalus, and fracture. This is an autosomal recessive disorder caused by mutations in either TCIRG1, CLCN7, or OSTM1 . Malformations are not a part of this disorder. We present a 6-month-old male, the first child between nonconsanguineous parents, who was referred to our clinic for limb defects. Findings prompting the referral included congenital left upper limb anomalies of syndactyly and radial-ulnar synostosis. There was an ipsilateral anterior rib defect, though there was no clinically appreciable hypoplasia of the pectoralis major. He also had a left low-lying, cross-fused kidney. Besides the limb anomalies, the patient presented in our clinic having signs of hydrocephalus. He had left facial nerve palsy and oculomotor abnormalities. The diagnosis of ARIO was made after hospitalization; radiographs demonstrated characteristic findings of diffuse osteosclerosis and periosteal thickening in all bones. The patient had surgical management for noncommunicating hydrocephalus with good results. The majority of cases with ARIO are compound heterozygotes. Reported homozygous patients most commonly result from a consanguineous mating or come from an isolated population (Costa Rica). Genetic testing of this patient revealed homozygosity for a rare mutation in TCIRG1, a subunit of the osteoclast vacuolar proton pump. Because this child was a product of a nonconsanguineous union, this was an unexpected result. To explain the malformations in this case, we postulated either uniparental disomy or a spontaneous contiguous gene deletion on one chromosome that included the TCIRG1 gene, which then unmasked a hemizygous recessive state. Subsequent sequence analysis of both parents for TCIRG1 mutations showed that each was a heterozygous carrier of their son's mutation. The presence of the limb and kidney anomalies complicated the diagnosis in this case. No other reported patients with ARIO have had similar birth defects. Without treatment, early demise secondary to bone marrow failure is predicted in nearly all cases. Associated features, natural history, and management recommendations for ARIO will be reviewed.